Analisis Pelanggaran Kolonialisme Terhadap Suatu Hak Yang Dimiliki Oleh Setiap Manusia - Faturohman Faturohman; Anggraeni Marshanda Putri; Mochamad Basit Alhaetami (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This correlation with the rights possessed by every human being cannot be separated, because this is something that is very inherent among them. Historical colonization has resulted in a fundamental economic, social and cultural oppression that humans have. For example, the practice of colonialism, which often involves political oppression such as the persecution of political activists. The economic exploitation that occurred under this colonial regime often resulted in social oppression, including exploitation of workers, injustice in the distribution of resources, and widespread poverty. Apart from that, colonialism also often causes racial and cultural discrimination, as well as the destruction of original cultural identity. By protecting and monitoring the rights of humans, this is often one of the main arguments in opposing and ending forms of oppression such as colonialization. The influence of colonialization on human rights is a very complex and very important matter in global history and politics. Colonial countries often implemented regulations that prohibited political participation and suppressed national independence movements or political activists who opposed colonial rule. Colonization can often lead to economic exploitation which can violate workers' rights, such as forced labor, low wages, and injustice in the distribution of economic resources. Colonial policies can often destroy native culture and also impose colonial culture on populations that have been dominated.